Commissioner board characteristics, ownership concentration, and corporate performance - Rahmat Setiawan; Irfan Handiliastawan; Rosmiati Jafar (University of Merdeka Malang, 2020)
This study analyzes the effect of board characteristics as a corporate governance mechanism on corporate performance with ownership concentration as a moderating variable. We conduct this study because there are still rarely studies that examine the effect of board characteristics on corporate performance by adding ownership concentration as a moderating variable. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2017 period with 350 observations. In this study, the characteristics of the board are proxied by the proportion of independent commissioners and the board commissioners’ size. Corporate performance is proxied by return on assets (ROA). By using multiple linear regression analysis, we found that the proportion of independent commissioners and the board commissioners’ size have a significant positive effect on ROA. Other results of this study indicate that the concentration of ownership significantly weakens the positive effect of the proportion of independent commissioners and the board commissioners’ size on corporate performance. JEL Classification: G32, G34 How to Cite:Setiawan, R., Handiliastawan, I., Jafar, R. (2020). Commissioner board characteristics, ownership concentration, and corporate performance. Jurnal Keuangan dan Perbankan, 24(2), 131-141.DOI: https://doi.org/10.26905/jkdp.v24i2.3827